PEMBANGUNAN KETENAGAKERJAAN PADA BIDANG PELATIHAN DAN PRODUKTIVITAS DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA DUMAI - Maulana, Ardiansyah; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Training which is done by the Employment and Transmigration Department of Dumai must be fit to the general training in order to produce the quality human resources. The Development of Employment in training and productivity section of employment and transmigration of Dumai is good because they provide the training based on the society’s demand and the burs effect. So that it produce the competence of human resources. The facilities Employment and Transmigration Department of Dumai are good enough and the chosen instructor are chosed by their competencies. The purpose of this research is to know the development of the Employment on training and productivity section at Employment and Transmigration of Dumai and find out factors which influence it.This research used theory of Werther & Davis says that development is defined by indicators of preparation, taken out, selection, development, treatment, and using. This research is classified as qualitative descriptive, the technique of collecting data in this research through observation and interview from everyone who are involved as informen.The result of this research shows that the development of Employment of Training and Productivity Section of Department of Employment and Transmigration of Dumai runs well. This is proved from the application of training based on the society’s demand and the needs of the market. Starting from recruitments, selection, and the chosen instructor and the activities of the tng. Factors which influences of the Development of Employment Training and Productity at Department of Employment and Transmigration of Dumai is finansial.Key words: Employment, Training, Employment Department